Budgetary impact of using BPaL for treating extensively drug-resistant tuberculosis. Issue 1 (6th January 2022) - Mulder, Christiaan; Rupert, Stephan; Setiawan, Ery; Mambetova, Elmira; Edo, Patience; Sugiharto, Jhon; Useni, Sani; Malhotra, Shelly; Cook-Scalise, Sarah; Pambudi, Imran; Kadyrov, Abdullaat; Lawanson, Adebola; et al.
Abstract : Introduction: Bedaquiline, pretomanid and linezolid (BPaL) is a new all oral, 6-month regimen comprised of bedaquiline, the new drug pretomanid and linezolid, endorsed by the WHO for use under operational research conditions in patients with extensively drug-resistant tuberculosis (XDR-TB). We quantified per-patient treatment costs and the 5-year budgetary impact of introducing BPaL in Indonesia, Kyrgyzstan and Nigeria. Methods: Per-patient treatment cost of BPaL regimen was compared head-to-head with the conventional XDR-TB treatment regimen for respective countries based on cost estimates primarily assessed using microcosting method and expected frequency of each TB service. The 5-year budget impact of gradual introduction of BPaL against the status quo was assessed using a Markov model that represented patient's treatment management and outcome pathways. Results: The cost per patient completing treatment with BPaL was US7142 in Indonesia, US4782 in Kyrgyzstan and US7152 in Nigeria – 57%, 78% and 68% lower than the conventional regimens in the respective countries. A gradual adoption of the BPaL regimen over 5 years would result in an 5-year average national TB service budget reduction of 17% (US128 780) in XDR-TB treatment-related expenditure in Indonesia, 15% (US700 247) in Kyrgyzstan and 32% (US1 543 047) in Nigeria. Conclusion: Our study demonstrates that the BPaL regimen can be highly cost-saving compared with the conventional regimens to treat patients with XDR-TB in high drug-resistant TB burden settings. This supports the rapid adoption of the BPaL regimen to address the significant programmatic and clinical challenges in managing patients with XDR-TB in high DR-TB burden countries.